A simulation method for compatibility between IMT-2020 base station with array antenna and DAB earth station - Tianqi HE; Tan WANG; Zhaojun QIAN; Peng LIU (Dianxin kexue)
The array antenna model and its parameters in ITU-R REC M.2101 were introduced in detail,and the model would be implemented in IMT deployment scenario modeling.Based on the lumped interference assessment method,the interference of the large-scale base station deployment to the central earth station at different distances was simulated,and the distance was protected by comparing the interference threshold.The research results can provide reference for future IMT system design and deployment,5G or related frequency planning.